Efektivitas Sosialisasi Kebijakan Pendidikan dalam Meningkatkan Kesadaran Guru dan Siswa - Amaluddin Tanjung; Tengku Darmansah; Dina Oktapia; Syafitri Halawa (Lembaga Pengembangan Kinerja Dosen, 2025)
Socialization is the most important process we go through, whether we realize it or not, in everyday life. Students' moral development is greatly influenced by policies in the field of education. wanting to confirm which method used to disseminate educational policies, the steps involved in the socialization process, socialization strategies, and the media used for socialization. In accordance with the initial conditions, this research was carried out using qualitative descriptive techniques. This is also seen from the perspective of educational policy socialization. Three stages should be considered when disseminating education policy, according to this research: preparation; imitation (or play); and action (or play). Social media, electronic media (such as CDs or compact disks), radio, television and radio, and other communication media can be used to promote educational policies.